On the realisation of voltage-mode filters using CDBA - Sedef, H; Acar, C (FACHVERLAG SCHIELE SCHON, 2000)
The authors propose two new configurations suitable for voltage-mode filter responses, it is possible to realise the most general nth-order and second-order voltage-mode transfer functions using these configurations. The first configuration uses a single current differencing buffered amplifier (CDBA) and RC:-RC decomposition technique to realise high order response. With this configuration the number of active elements is reduced to one compared to the previously reported method. The second configuration uses three CDBAs at most and state-space technique to realise second-order responses. The proposed filters seem to be versatile and suitable for the analogue signal processing. Independent parameters in the second configuration give flexibility to design. Proper choice of these parameters optimises the sensitivities.
Keywords: Engineering